Cardiotoxicity of anticancer treatments: Epidemiology, detection, and management. (26th February 2016) - Curigliano, Giuseppe; Cardinale, Daniela; Dent, Susan; Criscitiello, Carmen; Aseyev, Olexiy; Lenihan, Daniel; Cipolla, Carlo Maria
Abstract : Answer questions and earn CME/CNE Cancer and heart disease are the leading causes of morbidity and mortality in the industrialized world. Modern treatment strategies have led to an improvement in the chances of surviving a diagnosis of cancer; however, these gains can come at a cost. Patients may experience adverse cardiovascular events related to their cancer treatment or as a result of an exacerbation of underlying cardiovascular disease. With longer periods of survival, late effects of cancer treatment may become clinically evident years or decades after completion of therapy. Current cancer therapy incorporates multiple agents whose deleterious cardiac effects may be additive or synergistic. Cardiac dysfunction may result from agents that can result in myocyte destruction, such as with anthracycline use, or from agents that appear to transiently affect left ventricular contractility. In addition, cancer treatment may be associated with other cardiac events, such as severe treatment‐induced hypertension and vasospastic and thromboembolic ischemia, as well as rhythm disturbances, including QTc prolongation, that may be rarely life‐threatening. Early and late effects of chest radiation can lead to radiation‐induced heart disease, including pericardial disease, myocardial fibrosis, cardiomyopathy, coronary artery disease, valvular disease, and arrhythmias, in the setting of myocardial fibrosis. The discipline of cardio‐oncology has developed in response to the combined decision making necessary to optimize the care of cancer patients, whether they are receiving active treatment or are long‐term survivors. Strategies to prevent or mitigate cardiovascular damage from cancer treatment are needed to provide the best cancer care. This review will focus on the common cardiovascular issues that may arise during or after cancer therapy, the detection and monitoring of cardiovascular injury, and the best management principles to protect against or minimize cardiotoxicity during the spectrum of cancer treatment strategies.CA Cancer J Clin 2016;66:309‐325. © 2016 American Cancer Society .